Pajaritos Bridge Evaluation: a 50 year old concrete structure in an aggressive environment in the Gulg of Mexico - del Valle, Angélica; Pérez, José; Torres, Andrés; Martínez, Miguel (Revista Ingeniería de Construcción, 2006)
This investigation presents the results of the inspection performed on the Pajaritos Bridge as part of the activities for the Mexican bridge infrastructure evaluation project denominated National Plan for Bridge Corrosion Evaluation. This plan considers the evaluation of structural integrity of approximately 10000 bridges in the federal highway network. In this evaluation the following activities were performed: 1) A thoroughly visual examination; 2) A detailed inspection in two steps: a) Photographic and damage surveys; b) Mechanical, chemical and electrochemical testing; 3) A structural survey; 4) Results analysis and recommendations. It was found that the bridge deck was in need of major repairs and the bridge required the implementation of a cathodic protection system. All of the above made the bridge rehabilitation financially unfecesible, so it was recommended to tear down the bridge and to rebuild a new one. It was recommended that the new bridge design was based on durability requirements.